Multidimensional catalogs for systematic exploration of component-based design spaces - López, Claudia (2006)
Most component-based approaches to elaborate software require complete and consistent descriptions of components, but in practical settings components information is incomplete, imprecise and changing, and requirements may be likewise. More realistically deployable are approaches that combine exploration of candidate architectures with their evaluation vis-a-vis requirements, and deal with the fuzzyness of available component information. This article presents an approach to systematic generation, evaluation and re-generation of component assemblies, using potentially incomplete, imprecise, unreliable and changing descriptions of requirements and components. The key ideas are representation of NFRs using architectural policies, systematic reification of policies into mechanisms and components that implement them, multi-dimensional characterizations of these three levels, and catalogs of them. The Azimut framework embodies these ideas and enables traceability of architecture by supporting architecture-level reasoning, and allows architects to engage into systematic exploration of design spaces. A detailed illustrative example illustrates the approach.